(3ebGdI aj GdeMQc GdChds - (3CHh Sdje Hf WGgQ GdSLRj GdSLSJGfjs
(3ChdgG (B:s
(3Cf Chdi GdHMhK ai GdeMQc GdChd eG GQJHW GdcdGe ai GdfXQ GdWHjYi ajg HGdfXQ ajeG HYO GdWHjYi s
(3BNQgG (B:s
(3hGdeMQc GdChd GdPi Hg GdeJMQc GdChd eTJGb heTJHg Hg cGfG eNJdajf ai GdMO hgPG GdbOQ ai GdcdGe cGa ajeG GQOfG HjGfg JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdKGdKIs
(3GfXQg eY GdeNWhW Qbe (B301 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(3/253) s
Keywords: (3GdadSaI hGdefWbs